Comparative evaluation of adolescent repeated psychological or physical stress effects on adult cognitive performance, oxidative stress, and heart rate in female rats. (2nd January 2019) - Mousavi, Monireh-Sadat; Riazi, Gholamhossein; Imani, Alireza; Meknatkhah, Sogol; Fakhraei, Nahid; Pooyan, Shahriar; Tofigh, Nahid
Abstract: Multiple adult health problems are associated with adolescent stress. As the brain discriminates physical and psychological stressors by activation of different neural networks, we hypothesized that behavioral and physiological performance would be modulated differently based on the nature of the stressors. Thus, we studied the comparative effects of adolescent repeated physical and psychological stresses on adult cognitive performance, pro-oxidant-antioxidant balance (PAB) and heart rate in female rats. The aim was to differentiate disparate potency of chronic psychological and physical stresses leading to long-term behavioral and physiological alterations. Twenty-one female rats were divided randomly into three groups of seven rats each; control, physical, and psychological stress. Experimental rats were exposed to the stressors for five consecutive days (10 min daily) via a two-communication box. After verifying stress induction by serum corticosterone measurement, the rats were returned to their home cage for 6 weeks, until adulthood, elevated plus maze (EPM), forced swimming test (FST), Y-maze, object recognition task (ORT), and passive avoidance test (PAT) were used as five different behavioral tests to evaluate cognitive performance of each group. Serum PAB and heart rate were measured to assess long-term stress-induced physiological disorders. The results showed exposure to adolescent psychological stress resulted in a larger set of significant changes (in behavioral variation, oxidative stress, and elevated heart rate) 6 weeks post-stress compared to adolescent physical stress. Hence, mental health care in adolescence and therapies targeting PAB and heart rate could be prevention and treatment approaches to confront persistent adolescent stress-induced disorders. Lay summary The aim of our study on female laboratory rats was to differentiate disparate potency of chronic psychological and physical stresses in adolescence leading to long-term behavioral and physiological alterations. The results suggest that psychological stresses result in a greater extent of changes compared to physical stress. Adolescent chronic psychological stress may reveal itself in the form of certain behavioral and physiological variations in adulthood. Therefore, mental health care in adolescence could be a valuable prevention approach to confront a variety of adult stress-induced disorders.